Daily exposure to toxic metals through urban road dust from industrial, commercial, heavy traffic, and residential areas in Petaling Jaya, Malaysia: a health risk assessment - Shabanda, Ibrahim Sani; Koki, Isa Baba; Low, Kah Hin; Zain, Sharifuddin Md; Khor, Sook Mei; Bakar, Nor Kartini Abu (Springer Verlag (Germany), 2019)
Human health is threatened by significant emissions of heavy metals into the urban environment due to various activities. Various studies describing health risk analyses on soil and dust have been conducted previously. However, there are limited studies that have been carried out regarding the potential health risk assessment of heavy metals in urban road dust of < 63-μm diameter, via incidental ingestion, dermal contact, and inhalation exposure routes by children and adults in developing countries. Therefore, this study evaluated the health risks of heavy metal exposure via ingestion, dermal contact, and inhalation of urban dust particles in Petaling Jaya, Malaysia. Heavy metals such as lead (Pb), chromium (Cr), zinc (Zn), copper (Cu), and manganese (Mn) were measured using dust samples obtained from industrial, high-traffic, commercial, and residential areas by using inductively coupled plasma mass spectrometry (ICP-MS). The principal component and hierarchical cluster analysis showed the dominance of these metal concentrations at sites associated with anthropogenic activities. This was suggestive of industrial, traffic emissions, atmospheric depositions, and wind as the significant contributors towards urban dust contamination in the study sites. Further exploratory analysis underlined Cr, Pb, Cu, and Zn as the most representative metals in the dust samples. In accommodating the uncertainties associated with health risk calculations and simulating the reasonable maximum exposure of these metals, the related health risks were estimated at the 75th and 95th percentiles. Furthermore, assessing the exposure to carcinogenic and non-carcinogenic metals in the dust revealed that ingestion was the primary route of consumption. Children who ingested dust particles in Petaling Jaya could be more vulnerable to carcinogenic and non-carcinogenic risks, but the exposure for both children and adults showed no potential health effects. Therefore, this study serves as an important premise for a review and reformation of the existing environmental quality standards for human health safety. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.